Comparative Analysis of Structure with and without Seismic Load. Issue 1 (November 2021) - Patil, Abhishek K.; Solanke, Adarsh P.; Dabhekar, Kuldeep R.; Khedikar, Isha P.; Agrawal, Rahul; Rajput, Pratik P.; Chavan, Pranav V.
Abstract: Engineers are mostly adopting complex non-linear methods to research multi-storey residential apartment structure to withstand earthquake forces. This paper uses much simpler Equivalent Static method to analyse G+5 storey structure to repel earthquake forces using Staad pro software. The seismic analysis is further compared with non-seismic analysis of an equivalent structure using dead load + super load combination. it had been observed that the seismic results obtained consisted of significantly increased maximum moments and shear forces than the non-seismic analysis From past earthquakes it is proved that many of structure ar completely or partly broken because of earthquake. So, it's a necessity to figure out unstable responses of such structures. The main aim of the present work is to make a comparative study of seismic and non-Seismic structure. The analysis was performed as per the specification of IS codes IS 1893, IS 875, IS 456:2000.